Translation effects : the shaping of modern Canadian culture - Mezei, Kathy, 1947-; Von Flotow, Luise, 1951-; Simon, Sherry (McGill-Queen's University Press, 2014)
Much of Canadian cultural life is sustained and enriched by translation. Translation Effects moves beyond restrictive notions of official translation in Canada, analyzing its activities and effects on the streets, in movie theatres, on stages, in hospitals, in courtrooms, in literature, in politics, and across cafe tables. The first comprehensive study of the intersection of translation and culture, Translation Effects offers an original picture of translation practices across many languages and through several decades of Canadian life. The book presents detailed case studies of specific events and examines the reverberation and spread of their effects. Through these imaginative, at times unusual, investigations, the contributors unveil the simultaneous invisibility and omnipresence of translation and present a cross-cut of Canadian translation moments. Addressing the period from the 1950s to the present and including a wide scope of examples from medical interpreting to film dubbing, the essays in this book create a panoramic view of the creation of modern culture in Canada.